Lyrical I in Poetic Discourse of Carl Sandburg: A Linguo-Cognitive Approach - Babych, Vira; Nedainova, Iryna (Canadian Center of Science and Education, 2020)
The article deals with the linguo-cognitive analysis of the expression of the lyrical I in the poetic discourse of the prominent representative of the epoch of American modernism—Carl Sandburg. The lyrical I is understood as a poet’s imagery in which the image of a lyrical hero and the image of the author are united in a syncretic way and which represents a three-fold linguo-cognitive construct that incorporates a conceptual, pragmatic and verbal embodiments. Based on the analysis made in the research, the authors arrived at the conclusion that Carl Sandburg’s lyrical I describes a man of labor, depicts a difficult life of a man in an industrial city, shows the author’s appeal in support of a man’s fighting for his rights, for peace and freedom. In the poetic discourse of Carl Sandburg, the lyrical I is represented with the help of an urban figurativeness, a newspaper style of the language, a perfect skill of use of a blank verse resembling a song folklore, and a wide use of local expressions and dialectal words, colloquial language and prosaisms.
Keywords: lyrical I; poetic discourse; poetry of Carl Sandburg; linguo-cognitive analysis; epoch of American modernism